Long-Term Surgical Outcomes of Liver Resection for Hepatocellular Carcinoma in Patients With HBV and HCV Co-Infection: A Multicenter Observational Study - Jia, Hang-Dong; Liang, Lei; Li, Chao; Wu, Han; Wang, Hong; Liang, Ying-Jian; Zhou, Ya-Hao; Gu, Wei-Min; Fan, Xin-Ping; Zhang, Wan-Guang; Chen, Ting-Hao; Chen, Zhi-Yu; et al. (Frontiers in Oncology, 2021)
Background Hepatocellular carcinoma (HCC) is one of the most serious consequences of chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infection. This study sought to investigate long-term outcomes after liver resection for HCC among patients with HBV/HCV co-infection (HBV/HCV-HCC) compared with patients with HBV infection (HBV-HCC). Methods Patients who underwent curative-intent liver resection for HCC were identified from a multicenter Chinese database. Using propensity score matching (PSM), patients with HBV/HCV-HCC were matched one-to-one to patients with HBV-HCC. Overall survival (OS) and recurrence-free survival (RFS) were compared between the two groups before and after PSM. Results Among 2,467 patients identified, 93 (3.8%) and 2,374 (96.2%) patients had HBV/HCV-HCC and HBV-HCC, respectively. Compared with patients with HBV-HCC, patients with HBV/HCV-HCC were older, have poorer liver-related characteristics but better tumor-related characteristics. PSM created 88 pairs of patients with comparable liver- and tumor-related characteristics (all P > 0.2). In the PSM cohort, the 3- and 5-year RFS rates in patients with HBV/HCV-HCC were 48.3% and 38.9%, which were significantly poorer than patients with HBV-HCC (61.8% and 49.2%, P = 0.037). Meanwhile, the 3- and 5-year OS rates in patients with HBV/HCV-HCC were also poorer than patients with HBV-HCC (65.4% and 51.1% vs. 73.7% and 63.0%), with a difference close to be significant between them (P = 0.081). Conclusion Comparing to patients with HBV-HCC, liver resection resulted in relatively poorer long-term surgical outcomes in patients with HBV/HCV-HCC.